Vocational Teachers’ Insights on Artificial Intelligence and Computational Thinking Integration - Majid, Nuur Wachid Abdul; Barri, Muhamad Akda Fathul; Sari, Ayu Permata; Sodikin, Reisa Aulia; Azman, Mohamed Nor Azhari; Prestoza, Mark Jhon Ramos (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This qualitative case study investigates vocational teachers' perceptions of artificial intelligence and computational thinking integration in Indonesian secondary education. Seven vocational high school teachers from West Java Province participated through semi-structured interviews, non-participant observations, and document analysis following artificial intelligence training. The study employed an interactive analysis model to examine teachers' attitudes, concerns, and implementation strategies regarding artificial intelligence in educational contexts. Findings reveal positive teacher perceptions of artificial intelligence as a learning support tool, with applications ranging from creative media production to technical programming assistance. However, significant ethical and pedagogical concerns emerged, including academic integrity challenges, potential student dependency, inadequate prompt engineering skills, and risks of learning dehumanization. Teachers developed sophisticated guidance strategies, positioning artificial intelligence as a verification tool while maintaining human agency in learning processes. Supporting factors included personal initiative and professional learning communities, while barriers encompassed limited infrastructure, absence of formal guidelines, and varied digital competencies. The research contributes to understanding artificial intelligence adoption challenges in Indonesian vocational education and provides insights for implementing artificial intelligence skills curriculum policy. Results of the research are: (1) educators acknowledge significant advantages of AI integration, especially in improving technical learning experiences and promoting innovative educational endeavors, the integration of AI and computational thinking in the learning process must also prioritize the appropriate pattern aspects and requires clear guidance from stakeholders so that it can be implemented in the learning process; (2) ethical and pedagogical issues arise as significant obstacles, encompassing abuses of academic integrity, threats of student dependency, insufficient prompt engineering skills, and the potential dehumanization of learning experiences; (3) educators demonstrate significant adaptability by formulating advanced guiding systems that utilize AI as a verification and support mechanism while maintaining human agency in educational decision-making.